A digital tool to teach circular economy: an outlook about consumption module in DiGiTOOL to CE - Moreira, S.; Santos, M.; Xara-Brasil, Duarte; Carvalho, Luísa Cagica; Pinto, S.; Silva, C. (IV Jornadas científico-pedagógicas de inovação e sustentabilidade, 2022)
This research aims to discuss which topics must be considered to develop an innovative online module course focused on consumption in the perspective of Circular Economy. The course itself will help Higher Education Institutions to implement digital education solution into their curricula. The Erasmus + DiGiTOOL_to_CE project - Inclusive Digital Education - a Tool to Understand Circular Economy includes European experts from Albania, Italy, Latvia, Lithuania, and Portugal that are cocreating different modules on the subject. This process includes content development, e-course implementation, test on students and revision of the e-course module. The development of a comprehensive and coherent course, using a digital platform and including contributions from a diverse group of experts from different backgrounds and nationalities is a very complex task, especially with all the current travel and physical interactions restrictions related with COVID-19. It was thus necessary to use adequate platforms – as MIRO – and common templates for modules and storyboards, in apparel with a systematic interaction between all the members. This experience shows the potential to use all existing know-how and technological infrastructure for the development of the competencies in different research areas and improve our interaction skills in this international and mostly remote environment.